How does the digital economy affect corporate business credit supply? - Chen, Xiaohui; Cheng, Xiang (Journal of Business Economics and Management, 2024)
Business credit supply entails a firm providing credit to its customers as a means to gain a competitive edge. The advent of the digital economy has brought about profound changes in business practices. In this context, it becomes crucial to examine how the digital economy impacts the business credit supply of enterprises. This study employs a theoretical framework to derive insights and carries out an empirical analysis using the City Digital Economy Development Index spanning from 2008 to 2021, along with data from A-share listed companies in Shanghai and Shenzhen. The objective is to explore the influence of the digital economy on corporate business credit supply and its underlying mechanisms. The findings reveal that the digital economy can enhance corporate business credit supply by reducing the incidence of bad debt, thus enabling companies to extend more credit to their customers. This research contributes empirical evidence for understanding the microeconomic impact of the digital economy, while also providing theoretical insights to advance the development of the digital economy and optimize the allocation of financial resources, thereby alleviating corporate financing constraints.